HUBUNGAN KEPEMIMPINAN KEPALA DESA DENGAN KINERJA PERANGKAT PEMERINTAH DESA MAMUYA KECAMATAN GALELA INDUK KABUPATEN HALMAHERA UTARA - LAKO, ENTI SUSAN IRAWATI; Rumapea, Patar; Lengkong, Florence Daicy (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACK : The purpose of this study was to determine the relationship between the leadership of the village head and village government performance in the village of Galela District Parent Mamuya North Halmahera. The study was designed as a descriptive exploratory study. The respondents were 35 comprises: the village head and village, administrators BPD, LPM board, PKK, and community leaders / religious / customary in the village Mamuya. Data collection instrument was a questionnaire in the form of structured questionnaire.Data were collected for testing hypotheses are primary data sourced directly from responden.Teknik analysis used for hypothesis testing is statistical analysis chi-square and contingency coefficient. The results of chi-square analysis and contingency coefficient to the conclusion that although the leadership of the village head significantly associated with the performance of village government. This means that the leadership of the village head related to the performance of village government; the better the leadership of the village head, the better the performance of village government.Based on the results of these studies suggested that the leadership of the Village Head Mamuya improved quality, both in performing its duties and responsibilities in the village as well as decision-making, coordinating tasks and work of the village, establish effective communication with the village, as well as oversee or supervise the implementation of the tasks of the village.Keywords: leadership of the village head, village government performance